EUROPEAN FUNDS HELP ROMANIAN AGRICULTURE (World Science, 2020)
The EU Structural Funds are managed by the European Commission and are intended to finance structural assistance measures at Community level, with the aim of promoting regions with developmental delays, reconverting areas affected by industrial decline, combating long-term unemployment, employing young people or promoting rural development. The European Union is first and foremost an economic union. The central goal is to improve economic performance, including poverty reduction. Cohesion policy is the basic policy of the Structural Funds and is a key element in achieving the central goal.